2008
DOI: 10.1186/1472-6750-8-85
|View full text |Cite
|
Sign up to set email alerts
|

Generation of potent neutralizing human monoclonal antibodies against cytomegalovirus infection from immune B cells

Abstract: Background: Human monoclonal antibodies (mAbs) generated as a result of the immune response are likely to be the most effective therapeutic antibodies, particularly in the case of infectious diseases against which the immune response is protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 55 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…For example, the anti-respiratory syncytial virus mAb palivizumab and the anti-coronavirus mAb CR3014 have an IC 50 of 2 mg/ml (29,30), whereas the reported IC 50 of anti-influenza virus, antihuman CMV, and anti-West Nile virus mAbs range between 55 and 92 ng/ml (31)(32)(33). Therefore, the in vitro potency of 5F10 and 8B10 might be adequate for in vivo protection, which remains to be tested.…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…For example, the anti-respiratory syncytial virus mAb palivizumab and the anti-coronavirus mAb CR3014 have an IC 50 of 2 mg/ml (29,30), whereas the reported IC 50 of anti-influenza virus, antihuman CMV, and anti-West Nile virus mAbs range between 55 and 92 ng/ml (31)(32)(33). Therefore, the in vitro potency of 5F10 and 8B10 might be adequate for in vivo protection, which remains to be tested.…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…CD22-positive memory B cells were purified by magnetic selection (Miltenyi Biotech) from peripheral blood mononuclear cells (PBMCs) obtained from 1 patient with diffuse SSc designated PAM (47-year-old woman with esophagus and lung involvement, a Rodnan skin thickness score of 17, positivity for antinuclear antibodies and anti-Scl-70 antibodies, and negativity for anticentromere antibodies) (8). These cells (designated the PAM B cells) were immortalized using Epstein-Barr virus, as described previously (9)(10)(11). Three days postinfection, the cells were manually counted and seeded (5 cells/well) in 96-well plates in the presence of irradiated (30 Gy) allogenic PBMCs.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, direct and competitive ELISAs were performed with serum samples from 29 consecutive patients with SLE (SLE Disease Activity Index range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The distribution of PDGFRa binding in SLE serum was comparable to that in healthy control serum, as determined by direct ELISA with PDGFRa-His.…”
Section: Epitope Specificity Of Anti-pdgfra Autoantibodies In Sscmentioning
confidence: 99%
“…Using specific immunoabsorption to recombinant antigens and neutralization assays using fibroblasts as model target cells, it was estimated that 40 to 70% of the serum neutralizing activity is directed against gB (6). Other studies described human neutralizing antibodies specific for gB, gH, or gM/gN viral glycoproteins (6,14,26,29,34,41,52,60). Remarkably, we have recently shown that human sera exhibit a more-than-100-foldhigher potency in neutralizing infection of endothelial cells than infection of fibroblasts (20).…”
mentioning
confidence: 99%